Enabled SOA Transformation Leveraging open source principles. - Kochanik, Michael (SOA webservices journal.)
As numerous organizations are planning to embark on their first endeavors in service-oriented architecture (SOA), it is important to recognize that the necessary organizational transformation has as much to do with cultural transformation, as it has to do with open, Internet standards-based design. In fact, the very nature of how business and IT view each other's role and how the enterprise views its relationships with its marketplace partners and customers is being altered. Such cultural change has never come easily and represents a significant organizational dilemma.